STOCK MARKET REACTION TO NEWS: EVIDENCE FROM JUVENTUS REVISITED - Tanyue Sun; Maoguo Wu (European Scientific Journal, ESJ, 2015)
This paper examines a major influence on the stock prices of a publicly traded football club, Juventus Football Club S.p.A., a professional Italian association football club. The underlying financial theory applied and tested in this paper is the news model. The news model considers changes in stock prices the consequence of unexpected new public information. Applying the news model to the sport industry, it can be considered that unexpected match results affect the stock price of the club. In addition, following the reversed news model, whether major corporate governance related events have any influence on stock prices is tested. This paper contributes to the literature on the impact of unexpected public information on stock prices.